Implementing a Democratic Pedagogy in the Classroom: Putting Dewey into Practice - Sheryl MacMath (Canadian Society for Studies in Education, 2008)
A vignette detailing a discussion amongst elementary school teachers brings the ambiguity and challenges of implementing a democratic pedagogy into focus. Using this as a springboard, democratic pedagogy is explored through Dewey's three democratic dispositions: all human beings are morally equal, we are all capable of intelligent and well-informed opinions, and we can solve any problem if we work collaboratively. Taking these dispositions as the structural necessities for enacting a democratic pedagogy, this paper provides practical field examples of these three democratic dispositions as implemented by teachers.